Ensino colaborativo para aumento de repertório adequado de crianças com autismo em sala de aula - Pereira, Amanda Cristina dos Santos (2017)
Considering the importance of teaching appropriate behavioral repertoires for children with Autism Spectrum Disorder (ASD) in a wide variety of environments in which the child is inserted and the need for appropriate intervention for the school inclusion of this Special Education Target Audience (SETA) and the potential of the Collaborative Teaching, this study aimed to verify the effects of individualized teaching in establishing appropriate behavior in the classroom for children with ASD. Initiating collecting the complaints about the students's inadequate behavior and afterwards an elaboration of a program that aimed to modify the teaching techniques applied to the researcher and also the classroom teachers in a Collaborative Teaching way. The participants of this research were two children with ASD regularly enrolled in the first year of elementary school. The research was qualitative, in a collaborative type. The data collection procedure occurred in two stages. The first stage was the contact with the school staff to gather the demands/complaints for the future participating students and observation of the participants in their classroom in order to record the appropriate and inappropriate behaviors they emitted. In the second stage, an individual intervention plan was drafted by the researcher according to the concepts of Applied Behavior Analysis (ABA). The results show that both participants acquired new and adequate behavioral repertoires, decreased inappropriate behaviors in relation to stage 1 of this procedure and improved behaviors already learned The collaboration between the classroom teacher and the researcher developed well and according with what was expected in all the collaboration stages, it's possible that if the research project was longer the collaborative teaching would achieve all the collaboration criteria. It is concluded that the Applied Behavior Analysis (ABA) in school context offers a quality intervention for a quality intervention for this SETA. It is concluded that the Applied Behavior Analysis (ABA) in school context offers a quality intervention for this SETA.